THE IMPORTANCE OF FAMILY PLANNING IN PRIMARY HEALTH CARE - Pereira, Fagner Marques; Malaquias, Délio Tiago Martins; do Nascimento, Rafael Pinheiro; Furtado, Daniella Campos; Melo, Késia Rayser Sobrinho Tavares; Contar, Leonardo Haidar; de Oliveira, Nathália Carrijo; Guedes, Thaís; Machado, Alana Gonçalves; Consolin, Elis Muraro (Seven Editora, 2025)
Family planning is a fundamental strategy in primary health care (PHC), being essential for the promotion of sexual and reproductive health, the reduction of maternal and infant mortality rates, and the strengthening of gender equity. This integrative review aimed to analyze the scientific evidence on the importance of family planning in PHC, identifying its benefits and challenges. Twenty studies published between 2010 and 2023 were reviewed, and eight studies were selected in the PubMed, Scopus, and SciELO databases, using descriptors related to the theme. The results showed that the offer of diversified contraceptive methods, associated with sex education and qualified counseling, contributes significantly to the reduction of unplanned pregnancies and complications related to maternal and child health. In addition, these actions favor female empowerment and expand access to educational and professional opportunities. However, obstacles persist, such as scarcity of resources, lack of training of health teams, regional inequalities in access to services, and cultural and religious barriers that hinder adherence to contraceptive methods. Continuous training of health professionals, the strengthening of public policies, and the development of culturally sensitive strategies are essential measures to improve the effectiveness of family planning actions. It was concluded that the effective integration of family planning in PHC is essential to ensure informed reproductive choices, reduce social inequalities and improve the quality of life of populations, and it is necessary to carry out future studies that evaluate intervention models and public policies in different regional contexts. DOI: https://doi.org/10.56238/sevened2024.037-167